Impolite Strategies Identified in "Tiktok" User Comments - Zaqiah Bulgis Jodi (Paradigma Lingua, 2024)
Nowadays in modern technology, many features are provided to make people easily interact and give their opinions, e.g. column comments in social media. Unfortunately, some people use the features without filtering their language. In this case, the writer used the title “Impoliteness strategies found in Tiktok user comments”. This study then aims to analyze the type and function of impoliteness strategies used in social media, namely TikTok that had a lot of utterances that can be analyzed. The data were taken from the utterances of the TikTok user comments toward 20 videos which was posted by users who posted the video about Ariana Grande and Paige Nieman which the video consists of the differences and Paige Nieman as impersonate Ariana Grande in TikTok. The method used was descriptive qualitative. Then, to analyze the data, this study used Culpeper’s (1996) theory. The way data collected by selected the user accounts upload a video contents about Paige Nieman and Ariana Grande, then watched the video several times to identify whether the content invites negative utterances. And sorted out the comments which only contains impoliteness strategies. However, the results showed that out of 40 utterances containing impoliteness strategies, there were only four types of impoliteness strategies used in TikTok user comments, namely bald on record impoliteness, positive impoliteness, negative impoliteness, and sarcasm/mock impoliteness. The result also indicated that negative impoliteness, which consisted of 7 utterances, was the most frequently used, while sarcasm is the least frequent type of impoliteness strategy which was only 4 utterances. Moreover, this study found three functions of impoliteness strategies used in TikTok user comments. They are affective impoliteness, coercive impoliteness and entertaining impoliteness. Affective impoliteness is the most dominant function of impoliteness strategy, consisting of 28 data while entertaining is the least strategy occur in this research that is about 3 utterances.